A SINE-like insertion in intron 13 of the ATP7A gene is associated with a mild form of Menkes-like disease in a Cavalier King Charles Spaniel - Emily A Fulton; Cleo Schwarz; Vidhya Jagannathan; Tosso Leeb; Rodrigo Gutierrez-Quintana (Journal of Veterinary Internal Medicine, 2026)
Abstract A 7-month-old intact male Cavalier King Charles Spaniel was presented for persistent glucosuria despite normoglycemia, failure to thrive, chronic diarrhea, and cerebellar ataxia. Fanconi syndrome was diagnosed, but the neurologic abnormalities were not fully explained. As a consequence of the early onset Fanconi syndrome, a hereditary process was suspected. Whole genome sequencing identified a private hemizygous SINE-like insertion into the ATP7A gene, at the end of intron 13, near the start of exon 14. In humans, variants in ATP7A are associated with Menkes disease, a disorder of copper metabolism associated with a spectrum of clinical signs including progressive neurodegeneration and connective tissue abnormalities. Clinically affected dogs with variants in ATP7A have not been reported previously. Although this case appears to represent a mild phenotypic presentation of Menkes-like disease, it raises the possibility that copper disorders aside from copper-associated hepatitis might exist in dogs. Further genetic screening and phenotypic characterization of rare genetic variants associated with copper metabolism would be beneficial to expand our knowledge of copper disorders in dogs and allow potential early intervention and modeling for metabolic diseases in humans.